Molecular Immune Mechanism of Intestinal Microbiota and Their Metabolites in the Occurrence and Development of Liver Cancer - Bi, Chenchen; Xiao, Geqiong; Liu, Chunyan; Yan, Junwei; Chen, Jiaqi; Si, Wenzhang; Zhang, Jian; Liu, Zheng (Frontiers in Cell and Developmental Biology, 2021)
Intestinal microorganisms are closely associated with immunity, metabolism, and inflammation, and play an important role in health and diseases such as inflammatory bowel disease, diabetes, cardiovascular disease, Parkinson’s disease, and cancer. Liver cancer is one of the most fatal cancers in humans. Most of liver cancers are slowly transformed from viral hepatitis, alcoholic liver disease, and non-alcoholic fatty liver disease. However, the relationship between intestinal microbiota and their metabolites, including short-chain fatty acids, bile acids, indoles, and ethanol, and liver cancer remains unclear. Here, we summarize the molecular immune mechanism of intestinal microbiota and their metabolites in the occurrence and development of liver cancer and reveal the important role of the microbiota-gut-liver axis in liver cancer. In addition, we describe how the intestinal flora can be balanced by antibiotics, probiotics, postbiotics, and fecal bacteria transplantation to improve the treatment of liver cancer. This review describes the immunomolecular mechanism of intestinal microbiota and their metabolites in the occurrence and development of hepatic cancer and provides theoretical evidence support for future clinical practice.